2021
DOI: 10.1007/s10826-021-02051-w
|View full text |Cite
|
Sign up to set email alerts
|

Foster Families: A Systematic Review of Intention and Retention Factors

Abstract: Background: Compared to residential care, family foster care is the preferable type of alternative care for neglected or abused children as it provides a familiar context that supports children's developmental needs.New foster families are needed to care for these children. Objective: This systematic review aims to provide a critical analysis of the literature, identifying factors that explain the intention to become and to continue as a foster family. This review was performed following the PRISMA checklist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…These authors [ 74 ] analysing several studies, found that retention of foster families is closely related to factors within the child protection system, such as foster child characteristics; personal or family characteristics; and placement challenges, as well as relationship with services and professional support, in line with Portuguese studies, e.g., Diogo and Branco [ 75 ]. It is highlighted that not only close and warm relationships between professionals and foster families are relevant to helping them adequately deal with diverse challenges, but also specific training is needed—on empathic relationships to prevent significant problems between foster families and services, and on educational strategies, expectations of the foster child and Foster Care system, and promoting positive attitudes towards the foster child’s family and their life history [ 74 ].…”
Section: Addressing the Eu Strategy And The Guarantee Into The Portuguese Alternative Carementioning
confidence: 66%
See 1 more Smart Citation
“…These authors [ 74 ] analysing several studies, found that retention of foster families is closely related to factors within the child protection system, such as foster child characteristics; personal or family characteristics; and placement challenges, as well as relationship with services and professional support, in line with Portuguese studies, e.g., Diogo and Branco [ 75 ]. It is highlighted that not only close and warm relationships between professionals and foster families are relevant to helping them adequately deal with diverse challenges, but also specific training is needed—on empathic relationships to prevent significant problems between foster families and services, and on educational strategies, expectations of the foster child and Foster Care system, and promoting positive attitudes towards the foster child’s family and their life history [ 74 ].…”
Section: Addressing the Eu Strategy And The Guarantee Into The Portuguese Alternative Carementioning
confidence: 66%
“…For developing a foster care system, it is central to increase the number of foster families towards both strategies, recruiting new families as well as retaining the experienced families [ 37 ]. A systematic review [ 74 ] on recruitment and retention found that the intention to become a foster parent is largely influenced by motivational factors; personal and family characteristics; individual values and beliefs; social context influences; and perceived familiarity with the child protection system. Therefore, it suggests that recruitment campaigns should emphasize the intrinsic motivational factors and the resources needed to provide quality; appeal to moral responsibility, as well as to the difference that individuals could make in children’s lives; and disseminate accurate information (considering adequate knowledge about foster care is relevant in decisions to foster).…”
Section: Addressing the Eu Strategy And The Guarantee Into The Portuguese Alternative Carementioning
confidence: 99%
“…Somewhere between 30% (Ofsted, 2021) and 56% (Gibbs & Wildfire, 2007) of foster carers deregister within two years after approval. Two systematic reviews (Gouveia, Magalhães, & Pinto, 2021;Hanlon, Simon, Day, Vanderwill, Kim, & Dallimore, 2021) on the causes have both identified carers' relationship to professionals as one of the most important retention factors. Conflicts and communication difficulties with social workers (Gouveia et al, 2021) and lack of respect, emotional support, and sympathy (Hanlon et al, 2021) were among the most prominent factors reported to affect carers' willingness to continue fostering.…”
Section: First Concern: Unethical Interview Conductmentioning
confidence: 99%
“…Two systematic reviews (Gouveia, Magalhães, & Pinto, 2021;Hanlon, Simon, Day, Vanderwill, Kim, & Dallimore, 2021) on the causes have both identified carers' relationship to professionals as one of the most important retention factors. Conflicts and communication difficulties with social workers (Gouveia et al, 2021) and lack of respect, emotional support, and sympathy (Hanlon et al, 2021) were among the most prominent factors reported to affect carers' willingness to continue fostering. The relationship between carer and professionals begin during the investigative process and it could easily be argued that unethical interview conduct may further complicate the relationship and inflame potential conflicts.…”
Section: First Concern: Unethical Interview Conductmentioning
confidence: 99%
“…The recruitment and retention of resource parents are key factors in the delivery of quality foster care services [ 11 , 12 ]. Factors related to resource parent retention can be conceptualized at the levels of the child welfare system (e.g., resource parent retention is supported when there is sufficient training and ongoing communication with the child welfare practitioner), resource parent (e.g., social support, confidence, and sense of competence), and youth (e.g., positive youth-caregiver relationship, positive mental health) [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%